Konsep Penahanan dalam Sistem Hukum Indonesia - Al Farizi, Dizar (Lentera Hukum, 2016)
Detention is one of the forced efforts to enforce the law known in the criminal justice system, also, to arrest, search, confiscation, and wiretapping. The absolute authority possessed by law enforcement officials to detain a person suspected of committing a criminal act with the threat of a certain penalty makes detention very easy. Even though detention can be carried out, it must be carried out solely to examine the criminal case itself. Detention itself is an addition to an examination of a criminal case. The detention "can" be carried out against any suspect so that it is not an obligation to be carried out even if the criminal act suspected meets the requirements for detention. The protection of a person's civil liberties, especially concerning the legal process, will greatly depend on the clarity and detail of pretrial detention policies. Guarantee and protection of human rights in criminal procedural law rules have a very important meaning because most of the processes in this criminal procedural law lead to human rights restrictions such as arrest, detention, confiscation, search, and punishment which in essence are restrictions. HAM. KEYWORDS: The Concept of Detention, Indonesian Legal System.